College Algebra (11th Edition)

Published by Pearson
ISBN 10: 0321671791
ISBN 13: 978-0-32167-179-0

Chapter 2 - Section 2.3 - Functions - 2.3 Exercises - Page 200: 55



Work Step by Step

We know that: $f(x)=-3x+4$ Therefore: $f(2m-3)=-3(2m-3)+4$ $=-6m+9+4$ $=-6m+13$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.